Exploring Gethuk-Making Processes: An Ethnoscience Approach to Elementary Science Education - Amelia Putri; Ulya Fawaida; Annisa Lailis Sa'adah; Dhuwi Putri Meilinda; Ahmad Thoyyib Sertiansyach (Universitas Negeri Surabaya, 2025)
This study aims to enhance science learning in elementary schools by integrating an ethnoscience approach through the traditional process of making gethuk, a renowned food from Central Java. Employing a qualitative method with an ethnographic approach, this research seeks to uncover scientific concepts embedded in the gethuk-making process. Data were analyzed through three stages: data reduction, data presentation in narrative and tabular forms, and conclusion drawing. The findings reveal that the process of making gethuk involves key physical and chemical concepts, including physical changes, heat transfer, mechanical energy, and chemical transformations. These findings highlight the strong connection between local cultural practices and scientific principles, offering students a contextual and meaningful learning experience. The study emphasizes the importance of developing ethnoscience-based curricula, providing teacher training, and utilizing culturally relevant teaching materials to deepen students’ understanding of science concepts. Ultimately, integrating ethnoscience into science education not only promotes scientific literacy but also fosters cultural appreciation among elementary school students.